Given,
f(x)=e^sqrt(1/x^2 -x)f(x)=e√1x2−x
Let
y=f(x)y=f(x)
Then,
y=e^sqrt(1/x^2 -x)y=e√1x2−x
Let,
u=sqrt(1/x - x^2)u=√1x−x2
Then,
y=e^uy=eu
Differentiating both sides, wrt x
dy/dx = e^u . (du)/(dx)dydx=eu.dudx
Now,
u=sqrt(1/x - x^2)u=√1x−x2
Let,
v=1/x - x^2v=1x−x2
Then,
u=sqrtvu=√v
Differentiating both sides, wrt x
(du)/(dx) = 1/(2sqrtv)(dv)/(dx)dudx=12√vdvdx
Thus,
dy/dx = e^u 1/(2sqrtv)(dv)/(dx)dydx=eu12√vdvdx
Again,
v =1/x - x^2 v=1x−x2
Let
r = 1/xr=1x
Differentiating wrt x
(dv)/(dx)=-1/x^2dvdx=−1x2
s = x^2s=x2
Differentiating wrt x
(ds)/(dx)=2xdsdx=2x
now,
v=r-sv=r−s
Differentiating wrt x
(dv)/(dx)=(dr)/(dx)-(ds)/(dx)dvdx=drdx−dsdx
Thus,
(dv)/(dx)=-1/x^2-2xdvdx=−1x2−2x
Substituting for v & (dv)/(dx)v&dvdx in (du)/(dx)dudx
(du)/(dx) = 1/(2sqrtv)(dv)/(dx)dudx=12√vdvdx
(du)/(dx) = 1/(2sqrt(1/x - x^2))(-1/x^2-2x)dudx=12√1x−x2(−1x2−2x)
Substituting for u & (du)/(dx)u&dudx in dy/dxdydx
dy/dx = e^u . (du)/(dx)dydx=eu.dudx
dy/dx = e^(sqrt(1/x - x^2)) . (1/(2sqrt(1/x - x^2))(-1/x^2-2x))dydx=e√1x−x2.⎛⎜
⎜⎝12√1x−x2(−1x2−2x)⎞⎟
⎟⎠